The Later Wittgenstein and Moral Philosophy - De Mesel, Benjamin (Nordic Wittgenstein Studies,, 2018)
This book shows that Ludwig Wittgenstein's later philosophical methods can be fruitfully applied to several problems in contemporary moral philosophy. The author considers Wittgenstein's ethical views and addresses such topics as meta-ethics, objectivity in ethics and moral perception. Readers will gain an insight into how Wittgenstein thought about philosophical problems and a new way of looking at moral questions. The book consists of three parts. In the first part, Wittgenstein's later philosophical methods are discussed, including his comparison of philosophical methods to therapies. The book then goes on to explore how these methods give insight into Wittgenstein's ethical views. Readers will see how these are better understood when read in the light of his later philosophical thought. In the third part, Wittgenstein's later methods are applied to problems in contemporary moral philosophy, including a look at questions for moral advice. The author reviews and criticizes some of the secondary literature on Wittgenstein's later philosophical methods and indicates how the topic of the book can be developed in future research. There is something of value for readers of all levels in this insightful and well written volume. It will particularly appeal to scholars and students of Wittgenstein, of philosophy, and of ethics.